Effectiveness of metaverse-based family sculpture and meditation in reducing psychological distress - Yoo, Sang Hyun; Choi, Eun Jin; Yang, Hong Sik (Frontiers in Psychology, 2025)
IntroductionThe metaverse has demonstrated notable effectiveness in psychotherapeutic treatments. This study investigates the efficacy of a metaverse-based family sculpture technique in reducing psychological stress, anxiety, and depression.MethodsTraditional family sculpture methods, known for their ability to identify and address familial relationship dynamics, were adapted to a metaverse environment, facilitating immersive, nonphysical therapeutic interactions. Participants (n = 79) were divided into family sculpture, meditation, combined meditation and family sculpture, no-intervention, and placebo groups engaging in a wish lantern activity. Standardized tools (Generalized Anxiety Disorder-7, Patient Health Questionnaire-9, Perceived Stress Scale) measured psychological outcomes, followed by pre- and post-intervention assessments.ResultsThe combined meditation and family sculpture group exhibited the most significant reductions across all measures, demonstrating a synergistic effect between the two techniques. The family sculpture group effectively reduced anxiety, whereas the meditation group significantly decreased stress and depression. Satisfaction levels were the highest in the combined meditation and family sculpture group, reflecting participants’ positive perceptions of emotional stabilization and the usability of metaverse technology.DiscussionMetaverse-based interventions can expand access to psychotherapy, offering a novel and engaging platform for therapeutic innovation. Future research should explore larger sample sizes, extended intervention durations, and technical refinements to validate the long-term sustainability and effectiveness of these digital psychotherapeutic approaches.